Escalation in the relative prevalence of ciprofloxacin-resistant gonorrhoea among men with urethral discharge in two South African cities: association with HIV seropositivity. Issue 5 (2nd July 2008) - Lewis, D A; Scott, L; Slabbert, M; Mhlongo, S; van Zijl, A; Sello, M; du Plessis, N; Radebe, F; Wasserman, E
Abstract : Objectives: The objectives of this study were to assess the prevalence of ciprofloxacin-resistant gonorrhoea in two South African cities and to investigate the association between the isolation of ciprofloxacin-resistant Neisseria gonorrhoeae and the HIV serostatus of patients. Methods: Gonococci were cultured from endourethral swabs taken from consecutive men with urethritis attending clinics in Johannesburg and Cape Town. Minimum inhibitory concentrations (MIC) for ciprofloxacin and ceftriaxone were determined with E-tests. Isolates with a ciprofloxacin MIC of 1 mg/l or greater were defined as resistant and isolates with a ceftriaxone MIC of 0.25 mg/l or less were defined as susceptible. Rapid tests were used to screen and confirm the presence of HIV antibodies. Survey data from 2004 were used as a baseline to assess trends in gonococcal resistance to ciprofloxacin. Results: In 2004, the prevalence of ciprofloxacin resistance was 7% in Cape Town and 11% in Johannesburg. In 2007, 37/139 (27%) Cape Town isolates and 47/149 (32%) Johannesburg isolates were resistant to ciprofloxacin; in comparison with 2004 data, this represents 2.9-fold and 1.9-fold increases, respectively. All isolates were fully susceptible to ceftriaxone. There was a significant association between HIV seropositivity and the presence of ciprofloxacin-resistant gonorrhoea among patients (p = 0.034). Conclusions: Johannesburg and Cape Town have witnessed significant rises in the prevalence of ciprofloxacin-resistant gonorrhoea among men with urethritis. The resistant phenotype is linked to HIV seropositivity. There is now an urgent need to change national first-line therapy for presumptive gonococcal infections within South Africa.